Ambient temperature regulates root circumnutation in rice through the ethylene pathway: transcriptome analysis reveals key genes involved - Cai, Zeping; Dai, Yinuo; Jin, Xia; Xu, Hui; Huang, Zhen; Xie, Zhenyu; Yu, Xudong; Luo, Jiajia (Frontiers in Plant Science, 2024)
Plant roots are constantly prepared to adjust their growth trajectories to avoid unfavorable environments, and their ability to reorient is particularly crucial for survival. Under laboratory conditions, this continuous reorientation of the root tip is manifested as coiling or waving, which we refer to as root circumnutation. However, the effect of ambient temperature (AT) on root circumnutation remains unexplored. In this study, rice seedlings were employed to assess the impact of varying ATs on root circumnutation. The role of ethylene in mediating root circumnutation under elevated AT was examined using the ethylene biosynthesis inhibitor aminooxyacetic acid (AOA) and the ethylene perception antagonist silver thiosulfate (STS). Furthermore, transcriptome sequencing, weighted gene co-expression network analysis, and real-time quantitative PCR were utilized to analyze gene expressions in rice root tips under four distinct treatments: 25°C, 35°C, 35°C+STS, and 35°C+AOA. As a result, genes associated with ethylene synthesis and signaling (OsACOs and OsERFs), auxin synthesis and transport (OsYUCCA6, OsABCB15, and OsNPFs), cell elongation (OsEXPAs, OsXTHs, OsEGL1, and OsEXORDIUMs), as well as the inhibition of root curling (OsRMC) were identified. Notably, the expression levels of these genes increased with rising temperatures above 25°C. This study is the first to demonstrate that elevated AT can induce root circumnutation in rice via the ethylene pathway and proposes a potential molecular model through the identification of key genes. These findings offer valuable insights into the growth regulation mechanism of plant roots under elevated AT conditions.